2022
DOI: 10.3390/jof8090910
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Chitin Biosynthetic Pathway Results in Significant Changes in the Cell Growth Phenotypes and Biosynthesis of Secondary Metabolites of Monascus purpureus

Abstract: In this study, the gene monascus-5162 from Monascus purpureus LQ-6, identified as chitin synthase gene VI (chs6), was knocked out to disrupt the chitin biosynthetic pathway and regulate the biosynthesis of Monascus pigments (MPs) and citrinin. The results showed that the aerial hyphae on a solid medium were short and sparse after the deletion of chs6 in M. purpureus LQ-6, significantly reducing the germination percentage of active spores to approximately 22%, but the colony diameter was almost unaffected. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In addition, CHS I–III proteins are characterized by hydrophobic C-terminal and hydrophilic N-terminal regions containing a catalytic domain. In our laboratory, the chs protein-encoding gene Monascus_05162, detected in the M. purpureus LQ-6 genome, was identified as a CHS VI class enzyme based on the tertiary structure of the protein and conserved domain analysis [ 57 ].…”
Section: Chitin and Chitin Biosynthesis In Filamentous Fungimentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, CHS I–III proteins are characterized by hydrophobic C-terminal and hydrophilic N-terminal regions containing a catalytic domain. In our laboratory, the chs protein-encoding gene Monascus_05162, detected in the M. purpureus LQ-6 genome, was identified as a CHS VI class enzyme based on the tertiary structure of the protein and conserved domain analysis [ 57 ].…”
Section: Chitin and Chitin Biosynthesis In Filamentous Fungimentioning
confidence: 99%
“…Collectively, these findings indicate that CHS V and CHS VII genes are mainly required for normal hyphal growth, perithecia formation, and pathogenicity of filamentous fungi. Moreover, in our previous study, we observed that the deletion of the CHS VI gene in the filamentous fungus M. purpureus induced the development of balloon-tip-like structures in the hyphae, reduced hyphal branching efficiency, promoted hyphal elongation, and altered mycelial pellet formation during submerged fermentation [ 57 ]. Although CHS VI knockout reduced the maximum biomass obtained in submerged fermentation cultures by 19.63%, it did not alter the rate at which the colony diameter of M. purpureus grew [ 57 ].…”
Section: The Regulatory Effect Of Chitin Biosynthesis On the Cell Gro...mentioning
confidence: 99%
See 3 more Smart Citations